Real time compound ultrasound of the shoulder - De Candia, Alessandro (Radiology and oncology (Ljubljana), 2002)
Background. The purpose of the study was to determinate the value of the ultrasound real time compound imaging in the evaluation of supraspinatus tendon in subacromial impingement disease. Patients and methods. Preoperative ultrasound was performed on 180 shoulders in 157 patients with clin- ical suspicion of rotator cuff disease; 71 patients were surgically treated with acrimioplasty and cuff repair. The sonograms were obtained under static and dynamic examination using a 5-12 MHz high frequency lin- ear array probe, and compound real time elaboration of multiple images from different viewing angles (Sono CT - ATL). The supraspinatus morphology was classified into the following groups: the absence of tears, the presence of partial thickness tears and the presence of full thickness tears. In the absence of tears, the supraspinatus tendinopathy was classified into three classes according to the Neer stages. The ultrasound findings were compared to the surgical inspection results. Results. Ultrasound showed 32 (96.9%) out of 33 full thickness tears,only one false negative in a patient with large body, and 9 (75%) out of12 partial thickness tears. There were three false negative studies in supraspinatus tendons with superficial lesions. Ultrasound correctly showed 26(100%) out of 26 rotator cuffs with the absence of tear. Conclusions. Real time compound ultrasound is a useful tool in the evaluation of the supraspinatus tendon diseases; this technique permits the reduction of the presence of conventional ultrasound acoustic artefacts and provides necessary information for preoperative planning.
Keywords: diagnostika; rama; Ramenski sklep; Ramenski sklep, utesnitveni sindrom; Rotator Cuff; Rotatorna manšeta; Shoulder Impingement Syndrome; Shoulder Joint; Surgery; Ultrasonography; ultrazvočna diagnostika